Determining the Quinoa Water Requirement and Plant Response Coefficients to Water Stress in Different Growth Stages in Khuzestan Climate - F. Meskini-Vishkaee; A. Tafteh; M. Goosheh (علوم آب و خاک, 2023)
Salinity and water scarcity are limiting factors for sustainable agricultural production. The cultivation of resistant plants to environmental stresses is one of the important management factors for sustainable production. The objective of this study was to determine the water requirement and plant response coefficients to water deficit stress (Ky) in different growth stages under the Khuzestan province climate. This study was performed on the quinoa cultivar Titicaca in Ahvaz City in 2019 in a randomized complete block design with 13 treatments and three replications. Treatments include full irrigation and application of three levels of water deficit stress (30, 50, and 70% of allowable soil moisture depletion) at four different stages of plant growth. The duration of the initial, developmental, middle, and late growth stages of quinoa was 24, 28, 32, and 18 days, respectively (total growth period=102 days). The highest quinoa yield was obtained in full irrigation treatment (3700 kg ha-1) with a water requirement of 312 mm. Plant response coefficient to water deficit stress in the initial, developmental, middle, and late stages were 0.8, 0.65, 0.74, and 0.47, respectively. Although quinoa is a drought-resistance plant, it should be noted that the water stress in the two initial and middle stages (quinoa sensitive growth stages to water stress) reduces the quinoa yield significantly that should be considered in the planning of deficit irrigation.